SIKAP STAKEHOLDER TERHADAP INOVASI, IMPLIKASI, DAN DAMPAK DARI PENGGUNAAN BIOTEKNOLOGI PADA USAHA TERNAK SAPI PERAH - Amam Amam; Mochammad W. Jadmiko; Pradiptya A. Harsita; Mohammad S. Poerwoko (UNEJ e-Proceeding, 2018)
A research was carried out to formulate the stakeholder attitudes based on innovation, implications, and the impact of biotechnology use on dairy cattle business in Pujon District, Malang Regency and found the effect of the social environmental contribution that farmers feel on the use of biotechnology in dairy cattle business. The data was collected in the period of September to October 2018 using a survey method for 180 respondents as stakeholders. Data was processed using Fishbein's analysis approach. The results of the research indicate that stakeholder attitudes have a positive value on innovation, implications, and the impact of the use of biotechnology on dairy cattle business for upstream sectors, on farm and downstream sectors. The use of biotechnology in dairy cattle business is influenced by the government (23.50%), extension workers (37.33%), workers (12.67%), consumers (24.17%), and the social community (2.33%). The conclusion of this research is that the use of biotechnology in dairy cattle business gets a positive response from stakeholders. The process of innovation and the implications of biotechnology must involve various parties because it has an impact on social welfare.